Aplicación móvil para la toma de pedidos de comidas rápidas a domicilio en el restaurante "Super Pollo". - Carrera Yanez, Anderson Ismael (2017)
Nowadays the efficiency of the restaurants service is measured by the attention that it gives to the customer. The Super Pollo restaurant offers some delivery products at home through telephone calls in which many of the customers do not have the number to be able to access to this service, also they do not know about the products, prices and available promotions of the place, that is why they have to go to the restaurant in order to know about the services doing long rows for being attended, these aspects cause the loss of time at the moment of making ordering and of course, it makes the dissatisfaction in the customers, for that reason an alternative that contributes to resolve this problem is proposed. The principal aim of this project is to develop a software for taking the fast food orders to home, through the implementation of development methodologies with the purpose of contributing with the commercialization of products and makes easier the customers’ requests, which will allow to satisfy the requirements of both the owner and the customers. This application will allow to register the customers in order to visualize the products, prices and available promotions, when the customers are registered, the users can make their respective purchases according to the selected product , Also it will be able to visualize the total quantity of the purchase and it can generate the bill, the customers also have the possibility to cancel the purchase when they do not want it , the application will show other places where the restaurant is located with its respective address, the administrator will be able to visualize how many customers are registered, how many orders were made and can even generate the bill of each purchase made by the customer. Finally the administrator has the possibility to create, update and eliminate the products and promotions offered in the restaurant.